System of monitoring of Internet resources as instrument of digital marketing - N. B. Zemlyanskaya; D. A. Komonov; M. V. Sazonova (Вестник университета)
The concept of digital marketing as targeted and interactive marketing of goods and services which is directed to improve the operating mechanism of sales of products through the application of different digital technologies has been considered. Working process with information, necessary for improvement of content of the website and optimization of sales propositions has been shown. The main indicators of web analytics, including its analytical cycle have been considered in detail. The fundamental objectives, tools and services of web analytics, allowing to organize effectively its work, have been determined.